Pengaruh Pelatihan Deteksi Dini pada Kader Terhadap Peningkatan Pengetahuan Tentang Pelaporan Jumlah Kasus Gangguan Jiwa: Literatur Review - Amin Suliah; Sri Wahyuni; Bayhakki Bayhakki (Universitas Pahlawan Tuanku Tambusai, 2025)
Mental health is a condition in which an individual is physically, mentally, spiritually, and socially capable, thus being aware of their ability to cope with stress, be productive at work, and contribute positively to society. Knowledge among community health workers (kaders) is essential for reporting the number of mental disorder cases. This study uses a systematic literature review approach aimed at examining the effect of early detection training for kaders on improving their knowledge regarding the reporting of mental disorder cases. Literature was collected from several widely used and publicly accessible scientific databases, including PubMed and Google Scholar. The keywords used in the search included: “Early Detection Training,”,“Improving Kader Knowledge”,“Mental Disorder Cases” and “Mental Disorder Case Reporting.” From 137 articles identified, a selection process was conducted based on inclusion and exclusion criteria, resulting in 5 articles that were analyzed in depth. The findings indicate that early detection training has a positive impact on increasing kader knowledge about mental disorder cases. Through proper training, kaders gain a better understanding of the early signs and symptoms of mental disorders, risk factors, and the importance of early referral and intervention. Keywords: Early Detection Training, Improving Kader Knowledge, Mental Disorder Cases, Mental Disorder Case Reporting.